Strong or weak acid, which is more efficient for Beckmann rearrangement reaction over solid acid catalysts?1. Issue 7 (22nd July 2015) - Chu, Yueying; Ji, Peng; Yi, Xianfeng; Li, Shenhui; Wu, Peng; Zheng, Anmin; Deng, Feng
<x xml:space="preserve">Abstract</x> The effects of Brønsted acid strength and pore confinement on the Beckmann rearrangement reaction over solid acid catalysts have been explored.